The right to development versus environmental protection in South Africa - Mafungayika, Duduzile Grace (University of Limpopo (Turfloop Campus), 2009)
This research investigates the relationship between the right to development and the right to the environment. An overview of the legislative framework aimed at facilitating development and environmental protection is discussed. The right to development is aimed at improving the quality of life and living conditions of ordinary people. On the other hand, the right to the environment has as its purpose the conservation and prudent utilisation of natural resources. Theoretically, the two rights are at loggerheads. However, at the centre of these rights is the concept of sustainable development. Sustainable development harmonises the implementation of developmental activities and environmental protection, by compelling government authorities and developers to consider environmental issues when implementing development projects. Public participation is vital in environmental law as it ensures that the public is well informed about development projects that may have adverse effects on the environment. Public participation in development projects is part of the Environmental Impact Assessment process (EIA). A case study of a local township was conducted to illustrate the importance of public participation and the acceptance of the right to development and the right to the environment as justiciable human rights in South Africa. The study revealed that local government officials lack the necessary knowledge and skills to implement development and environmental laws at local community level. This results in non- compliance with the existing environmental laws by developers. It is concluded that right to development and the right to the environment co-exist and are mutual reinforcing. Therefore, failure to ensure proper implementation of the two rights may result in short- lived and unsustainable development, projects and programs. It is concluded further that non-compliance with the EIA procedure defeats the concept of public participation as embodied in environmental law and international environmental instruments. It is recommended that the government should equip its officials and citizens with skills and knowledge on how environmental laws operate and should be implemented.
Thesis (M.Law. (Development and Management)) --University of Limpopo, 2009
Keywords: Development; Environment; Legislation; 344.04602646; Cities and towns -- Growth; City planning; Environmental protection; Environmental law